2019
DOI: 10.3390/polym11030516
|View full text |Cite
|
Sign up to set email alerts
|

Slow Dynamics of Ring Polymer Melts by Asymmetric Interaction of Threading Configuration: Monte Carlo Study of a Dynamically Constrained Lattice Model

Abstract: Abnormally slower diffusional processes than its internal structure relaxation have been observed in ring polymeric melt systems recently. A key structural feature in ring polymer melts is topological constraints which allow rings to assume a threading configuration in the melt phase. In this work, we constructed a lattice model under the assumption of asymmetric diffusivity between two threading rings, and investigated a link between the structural correlation and its dynamic behavior via Monte Carlo simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This observation indicates that the dynamics in ring polymers without chain ends becomes spatially homogeneous and the mechanism of the chain motion is essentially different from the reptation model for linear polymers A plausible key feature for topological constraints in ring polymers is an inter-ring threading event. [39][40][41][42][43][44][45][46][47] In particular, Michieletto et al have proposed the "random pinning" procedure, wherein some fractions of rings are frozen, to investigate the role of threadings on the dynamics. 44 They demonstrated that random pinning can enhance the glass-like heterogeneous dynamics in ring polymers.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…This observation indicates that the dynamics in ring polymers without chain ends becomes spatially homogeneous and the mechanism of the chain motion is essentially different from the reptation model for linear polymers A plausible key feature for topological constraints in ring polymers is an inter-ring threading event. [39][40][41][42][43][44][45][46][47] In particular, Michieletto et al have proposed the "random pinning" procedure, wherein some fractions of rings are frozen, to investigate the role of threadings on the dynamics. 44 They demonstrated that random pinning can enhance the glass-like heterogeneous dynamics in ring polymers.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…Lee and Jung [103] used lattice Monte Carlo simulations to study the connection between slow diffusional processes in melts of polymer rings and topological constraints associated with threading events between different ring molecules. Monte Carlo simulations on a face-centered-cubic lattice were employed by Suzuki and collaborators in a series of papers [104][105][106][107][108] to study: (a) the size and conformation of non-concatenated polymer rings in the melt state [104], (b) molecular conformations of trivial, 3 1knot, and 5 1 -knot ring polymers at their theta points [105,106], (c) the temperature dependence of the second virial coefficient of ring polymers [107], and (d) the size and conformation of catenated ring polymers in dilute solution, over a wide range of chain lengths [108].…”
Section: Polymer Rings and Knotsmentioning
confidence: 99%
“…The transition between ballistic and diffusive motion is highly dependent on the properties and structure of a particular liquid [13]. Unusually long ballistic motions have been reported by research groups studying particles in polymer melts [14][15][16], polymer-grafted gold nanoparticles [17], polymer rings [18], DNA [19], enzymes [20], and even bacteria [21].…”
Section: Introductionmentioning
confidence: 99%